Unitary operation mass transfer modelling during the deep fat frying processes of the creole potato (Solanum phureja Juz. & Bukasov) - Juan Carlos Lucas Aguirre; Jose fernando Vasco Leal; José Daniel Mosquera-Artamonov; Liceth Cuellar-Nuñez; Victor Dumar Quintero Castano (Acta Agronómica)
The main objective of this research was to developing mathematical models to predict the behavior of quality attributes in Creole fried slices of creole potato (Solanum phureja). Frying conditions used were: temperature 170 and 190 ° C, 1.5 times and 3.5 min with a slice thickness of 1.5 mm; taking as response variables the final product color, texture, moisture content and percentage fat. The experimental design used was completely randomized with a factorial arrangement 22 (temperature and time) with three replicates per treatment. It was shown that color, moisture and fat variables showed no problems in the assumptions of normality and equal variances allowing use ANOVA. For the mathematical modeling of the texture variable, was initially necessary to use a transformation unit and subsequently, to conduct an ANOVA. The analysis showed three significantly variables statistical models for moisture, fat percentage, and texture. With respect to color, the controllable factors were no performed any statistical significance (p> 0.05). In addition, a correlation coefficient of 35.91% was performed. The mathematical models satisfactorily allowed predict the behavior of the response variables.